Delegation of Authority as an Optimal (In)complete Contract - Andreas Roider (Institute for the Study of Labor (IZA), 2004)
The present paper aims to contribute to the literature on the foundations of incomplete contracts by providing conditions under which simple delegation of authority is the solution to the complete-contracting problem of the parties. We consider a hold-up framework where both parties profit from an investment that raises the value of an asset. Delegation turns out to be optimal if (i) the decision-dependent parts of the payoffs of the parties are linear in the asset value, and (ii) decisions have no investment-independent effect. If overinvestment might be an issue, delegation, however, with restricted competencies is optimal if some additional continuity requirements are met.
Keywords: L14; D23; D82; L22; 330; delegation; decentralization; authority; incomplete contracts; hold-up; property rights; Kooperative Führung; Dezentrale Organisation; Unvollständiger Vertrag; Eigentumsrechtstheorie; Investition; Sunk Costs; Theorie